2019
DOI: 10.31688/abmu.2019.54.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Improving the drug compliance of hypertensive patients in primary care: importance of health education and self-management

Abstract: L'amélioration de la compliance à la médication chez les patients hypertendus dans les soins de santé primaires: importance de l'éducation à la santé et de l'auto-gestion Introduction. Compte tenu de la prévalence et de la charge associée de l'hypertension, il est nécessaire d'obtenir un contrôle optimal de la pression artérielle et d'améliorer les résultats pour ces patients. Mais il a été noté que l'observation du traitement antihypertenseur est très mauvaise, conduisant à un contrôle non optimal de la malad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Despite that behavioral change is a highly effective prevention strategy, patient motivation and adherence to lifestyle recommendations are an obstacle to preventive care [12], [13]. A multifaceted approach at primary care settings, including controlled physical exercise, follow-up calls, and prescription reminders in addition to ongoing FP services, can improve patient adherence to prescribed medications and behavioral changes, while addressing barriers such as time and resource constraints for FPs [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that behavioral change is a highly effective prevention strategy, patient motivation and adherence to lifestyle recommendations are an obstacle to preventive care [12], [13]. A multifaceted approach at primary care settings, including controlled physical exercise, follow-up calls, and prescription reminders in addition to ongoing FP services, can improve patient adherence to prescribed medications and behavioral changes, while addressing barriers such as time and resource constraints for FPs [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…Poor control of arterial hypertension in diabetic patients determines an elevated risk of acute cardiovascular events, such as myocardial infarction or stroke (24)(25)(26). GLP-1 agonists, such as exenatide and liraglutide, demonstrated in a meta-analysis a beneficial effect on reducing blood pressure in diabetic patients in the early phase of treatment, not related to weight reduction, probably by inhibition of the renin-angiotensin-aldosterone system, improvement of endothelial function and direct activation of specific receptors in the vascular tissue (27).…”
Section: Evidence Of Cardiovascular Effects Of Glp-1 Agonistsmentioning
confidence: 99%
“…The existing system did not contribute to the reduction of self-referral to specialized medical services. Studies have confirmed that this situation may have a negative effect on the patient's treatment 33 .…”
Section: Discussionmentioning
confidence: 98%